Starch Functional Properties and Resistant Starch from Foxtail Millet [Setaria italica (L.) P. Beauv] Species - Bangoura, Mohamed Lamine; Nsor-Atindana, John; Ming, Zhou Hui; Wei, Peng; Mothibe, Kebitsamang Joseph; Xue, Zhu Ke (Pakistan Journal of Nutrition, 2012)
The study evaluated physicochemical and content of Resistant Starch (RS) of starches isolated from defatted white foxtail millet and yellow foxtail millet by alkaline extraction. The characteristic of the isolated starches were compared with those of commercial corn starch (CCS). The extraction yielded 42.10% and 39.29% (dry basis) of starch respectively, for white and yellow foxtail millets. The amylose content was highest (35.80mg g-1) in the Yellow Foxtail Starch (YFS) followed by White Foxtail Starch (WFS) which recorded 34.92mg g-1 and CCS (33.98mg g-1) with significant difference (p